2012
DOI: 10.1002/ptr.4616
|View full text |Cite
|
Sign up to set email alerts
|

3‐O‐Acetyloleanolic Acid Induces Apoptosis in Human Colon Carcinoma Hct‐116 Cells

Abstract: The cytotoxic effect of 3-O-acetyloleanolic acid, an oleanolic acid derivative isolated from the seeds of Vigna sinensis K., was investigated in human colon carcinoma HCT-116 cells. 3-O-acetyloleanolic acid dose-dependently inhibited the viability of HCT-116 cells. Apoptosis was characterized by detection of cell surface annexin V and sub-G1 apoptotic cell populations. The number of immunostained cells with annexin V-FITC was increased after treatment with 3-O-acetyloleanolic acid. The sub-G1 cell population w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Recently, triterpenoids such as celastrol and ursolic acid have been suggested to potentiate tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis through upregulation of DR4 and/or DR5 (16,17). In our previous study, 3-O-acetyloleanolic acid was also shown to induce apoptosis in HCT-116 cells, which is mediated by upregulation of DR5 (18). TRAIL is a TNF family member showing anti-tumor activity in various cancer cell types as well as minimal cytotoxicity to normal cells and tissues (19).…”
Section: Discussionmentioning
confidence: 94%
“…Recently, triterpenoids such as celastrol and ursolic acid have been suggested to potentiate tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis through upregulation of DR4 and/or DR5 (16,17). In our previous study, 3-O-acetyloleanolic acid was also shown to induce apoptosis in HCT-116 cells, which is mediated by upregulation of DR5 (18). TRAIL is a TNF family member showing anti-tumor activity in various cancer cell types as well as minimal cytotoxicity to normal cells and tissues (19).…”
Section: Discussionmentioning
confidence: 94%
“…Detailed mechanistic insights revealed that 3- O -acetyloleanolic acid upregulated DR5 expression in the treated colon cancer cells. Indeed, also markedly enhanced levels of caspase-8 and caspase-3 were noticed in those cells [104]. …”
Section: Oleanolic Acid As Anticancer Agentmentioning
confidence: 99%
“…3- O -acetyloleanolic acid induced apoptosis in HCT-116 cells by an extrinsic caspase signaling cascade and by up-regulation of death receptor 5 (DR5) [40]. …”
Section: In Vitro Effects Of Oa and Its Synthetic Derivatives On Cmentioning
confidence: 99%